2016
DOI: 10.5487/tr.2016.32.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead Exposure on the Status of Reticulocyte Count Indices among Workers from Lead Battery Manufacturing Plant

Abstract: Earlier studies conducted on lead-exposed workers have determined the reticulocyte count (RC) (%), but the parameters of Absolute Reticulocyte Count (ARC), Reticulocyte Index (RI), and Reticulocyte Production Index (RPI) were not reported. This study assessed the effect of lead (Pb) exposure on the status of reticulocyte count indices in workers occupied in lead battery plants. The present cross-sectional study was carried out on 391 male lead battery workers. The blood lead levels (BLL) were determined by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(30 reference statements)
0
5
0
1
Order By: Relevance
“…Pada pajanan yang lama dengan kadar timbal yang tinggi, masa hidup eritrosit memendek dan dihubungkan dengan inhibisi pada pyrimidine 5nucleotidase yang selanjutnya menyebabkan anemia hemolitik yang ditandai dengan hasil hitung retikulosit (Kalahasthi and Barman, 2016). Hubungan kadar timbal darah dengan hasil hitung retikulosit diperoleh hasil p-value = 0,000, nilai p < 0,05 dengan tingkat kepercayaan 95% hal tersebut menunjukkan adanya korelasi yang signifikan antara kadar timbal darah dengan hasil hitung retikulosit serta menunjukkan hubungan yang kuat (r = 0,663) dan berpola positif artinya semakin tinggi kadar timbal darah maka semakin tinggi persentase hasil hitung retikulosit.…”
Section: Joimedlabsunclassified
“…Pada pajanan yang lama dengan kadar timbal yang tinggi, masa hidup eritrosit memendek dan dihubungkan dengan inhibisi pada pyrimidine 5nucleotidase yang selanjutnya menyebabkan anemia hemolitik yang ditandai dengan hasil hitung retikulosit (Kalahasthi and Barman, 2016). Hubungan kadar timbal darah dengan hasil hitung retikulosit diperoleh hasil p-value = 0,000, nilai p < 0,05 dengan tingkat kepercayaan 95% hal tersebut menunjukkan adanya korelasi yang signifikan antara kadar timbal darah dengan hasil hitung retikulosit serta menunjukkan hubungan yang kuat (r = 0,663) dan berpola positif artinya semakin tinggi kadar timbal darah maka semakin tinggi persentase hasil hitung retikulosit.…”
Section: Joimedlabsunclassified
“… 1 Occupational exposure to lead occurs through inhalation and ingestion. Recent studies on lead-battery manufacturing workers have reported high musculoskeletal disorders with markers of inflammation, 2 mucocutaneous changes, 3 oxidative stress, 4 altered serum magnesium fractions, 5 elevated blood lead levels (BLLs), 6 , 7 reticulocytosis, 8 altered genetic polymorphisms of δ-aminolevulinic acid dehydratase (ALAD), 9 impaired biogenic amino acids with neurobehavioral function, 10 genotoxicity, 11 impaired coagulation function, 12 health problems, 13 , 14 male reproductive function, 15 ocular changes, 16 impaired hematological parameters, 17 and altered calcium metabolism by inhibiting the kidney 1-𝛼-hydroxylase enzyme, which is required for 1, 25 dihydroxy-vitamin D 3 synthesis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…[1] In the body, Pb accumulates in erythrocytes, soft tissues (brain, kidney, and bone marrow), and mineralized tissue (bone, teeth). Literature states that workers exposed to Pb form Pb-battery manufacturing plant have reported the disturbances in epigenetic status,[2] oxidative DNA damage,[3] altered reticulocyte count,[4] oxidative stress,[5] biogenic amino acids with neurobehavioral changes,[6] gene polymorphisms of ALAD, glutathione peroxidase (GPx), paraoxonase and metallothionein-4 activities [789], and calcium metabolism with bone mineral density. [10] Pb also affects several body systems, which include blood pressure,[11] ocular changes,[12] coagulation,[13] osteoporosis risk [14] poor dental health,[15] hearing loss [16] cardiovascular,[17] neuropathy,[18] renal,[19] hepatic [20], and reproductive [21] abnormalities.…”
Section: Introductionmentioning
confidence: 99%